Digital Transformation and the Performance of Government Accountants: Toward an Integrated Model of Competence, Leadership, and Performance Measurement - Omar, Muhamad Khalil; Aluwi, Ainie Hairianie; Hussein, Norashikin (Advances in Social Sciences Research Journal, 2026)
This study examines the influence of digital transformation on job performance among accounting personnel in Malaysia’s public sector, with a specific focus on the Accountant General’s Department of Malaysia (JANM). The research is motivated by the growing need to understand how digitalization initiatives such as the iGovernment Financial Management Accounting System (iGFMAS) shape performance management and measurement practices within public financial management. Using a sequential mixed-method approach, the study begins with qualitative interviews to explore the implementation, benefits, and challenges of digital transformation, followed by a quantitative survey to validate the relationships among key constructs. The model investigates digital competence and leadership support as mediating factors linking digital transformation to job performance. Data will be collected from accounting officers across various grades (W1–W14) through purposive sampling, targeting at least 400 survey responses and 10–20 in-depth interview participants. Quantitative data will be analyzed using statistical software such as SPSS and structural equation modeling tools, while qualitative data will be analyzed thematically using NVivo. The study is expected to produce a performance management and measurement framework tailored to Malaysia’s digital public finance environment. Findings will offer practical insights for enhancing workforce competence, leadership engagement, and performance accountability in the context of digital transformation. The research contributes to both policy and practice by aligning human capital development with technology-driven performance improvement in the public sector.